2017
DOI: 10.1021/acsami.7b00805
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Assembly of α-Fe2O3 Nanorods on Multiwall Carbon Nanotubes as a High-Performance Sensing Material for Gas Sensors

Abstract: This paper presents a facile hydrolysis reaction and annealing for preparing a novel hierarchical nanoheterostructure via assembly of α-FeO nanorods onto multiwall carbon nanotubes (MWCNTs) backbones. The as-synthesized nanocomposites were characterized using XRD (X-ray diffraction), FESEM (Field emission scanning electron microscopy), TEM (Transmission electron microscopy), XPS (X-ray photoelectron spectroscopy) and BET (Surface Area and Porosity System). The observations showed uniform α-FeO nanorods approxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 115 publications
(52 citation statements)
references
References 45 publications
1
49
0
Order By: Relevance
“…concluded that short and small diameter CNTs perform better electrochemically, due to the insertion‐extraction speed of Li‐ions . The 3D CNTs‐CNFs nanomaterials displayed greater improvement in performance compared to their single compounds . Moreover, the production of the 3D CNTs grown‐CNFs also has many difficulties, such as in the control production parameters, the growth of carbon nanostructures, and the distribution of the CNTs on the CNFs, which can be the focus of future works.…”
Section: D Cnts/cnfs: Challenges and Solutionsmentioning
confidence: 98%
See 4 more Smart Citations
“…concluded that short and small diameter CNTs perform better electrochemically, due to the insertion‐extraction speed of Li‐ions . The 3D CNTs‐CNFs nanomaterials displayed greater improvement in performance compared to their single compounds . Moreover, the production of the 3D CNTs grown‐CNFs also has many difficulties, such as in the control production parameters, the growth of carbon nanostructures, and the distribution of the CNTs on the CNFs, which can be the focus of future works.…”
Section: D Cnts/cnfs: Challenges and Solutionsmentioning
confidence: 98%
“…The ratio I D /I G band is the main factor for evaluating the disorder and defect in the structure of carbon materials; the high ratio of I D /I G means high disorder degree and free defect. SWCNTs have low I D /I G ratio ,, . The ratio I D /I G band of the hierarchical 3D CNTs/CNFs (I D /I G =0.79) is lower than the ratio of pure CNFs and higher than CNTs (I D /I G =0.12) .…”
Section: Characterization Of Cnts Grown On Cnfsmentioning
confidence: 99%
See 3 more Smart Citations